A first systematic mapping study on combinatorial interaction testing for software product lines - Lopez-Herrejon, Roberto E.; Fischer, Stefan; Ramler, Rudolf; Egyed, Alexander (2015 IEEE Eighth International Conference on Software Testing, Verification and Validation Workshops (ICSTW), 2015)
Software Product Lines (SPLs) are families of related software systems distinguished by the set of features each one provides. Over the past decades SPLs have been the subject of extensive research and application both in academia and industry. SPLs practices have proven benefits such as better product customization and reduced time to market. Testing SPLs pose additional challenges stemming from the typically large number of product variants which make it infeasible to test every single one of them. In recent years, there has been an extensive research on applying Combinatorial Interaction Testing (CIT) for SPL testing. In this paper we present the first systematic mapping study on this subject. Our research questions aim to gather information regarding the techniques that have been applied, the nature of the case studies used for their evaluation, and what phases of CIT have been addressed. Our goal is to identify common trends, gaps, and opportunities for further research and application.